PENGEMBANGAN MODEL PERSIAPAN PENSIUN BAGI KARYAWAN NON-KEPENDIDIKAN DI UNIVERSITAS â€œXâ€ - Yuni Apsari, Florentina (Universitas Katolik Widya Mandala Surabaya, 2012)
The designs of Retirement Program that suit the employeesâ€™ needs should consider the employeesâ€™ job characteristics. Educational institution with two groups of workers: Educational employees such as teachers (lecturers) and non-educational employees, who handle administrative tasks, make each working group have different aspects of retirement preparation. This qualitative study aimed in finding designs of retirement preparation that suits the needs of non-educational employees in X University. The data obtained will then be used as a recommendation to plan retirement programs based on findings in the field. The research result shows particular aspects that employees should prepare in facing retirement age such as developing the proper mindset about retirement, the preparationn of economic aspects related to financial management and entrepreneurship, the preparation of psychological aspects, the preparation of physical health aspects, the preparation of social aspects by developing social support, and the understanding of the institution policies related to retirement.